GEOCHEMISTRY OF HYDROTHERMAL FLUIDS FROM THE ULTRAMAFIC-HOSTED LOGATCHEV HYDROTHERMAL FIELD, 15°N ON THE MID-ATLANTIC RIDGE: TEMPORAL AND SPATIAL INVESTIGATION - Schmidt K.; Koschinsky A.; Garbe-Schönberg D.; de Carvalho L.M.; Seifert R. (My University, 2007)
Mantle-derived ultramafic rocks commonly occur on the seafloor at slow-spreading axes and are tectonically emplaced along shear zones. Since the early 1990s, a growing number of hydrothermal systems have been detected in ultramafic settings. But chemical data for fluid compositions in active systems are still limited. Besides the Logatchev field at 15°N on the Mid-Atlantic Ridge (MAR), the only other active high-temperature (> 300 °C) hydrothermal field known to be strongly influenced by ultramafics is the Rainbow field at 36°N on the MAR. The field at Logatchev consists of six active vent sites at about 3000 m water depth, situated along a NW-SE-trending line with distances of 50-200 m between the individual sites. The vent sites were mapped in detail and re-sampled during two cruises in 2004 and 2005 using a ROV. The geochemical composition of the hydrothermal fluids is characterized by very high concentrations of dissolved methane and hydrogen (up to 3.5 mM and 19 mM, respectively) related to serpentinization processes in the reaction zone. Together with moderate Si concentrations of 9 mM, a depletion in B compared to seawater and Li concentrations lower than in basaltic systems, this fluid composition has been identified as characteristic signature of high-temperature hydrothermal fluids reacting with ultramafic rocks. However, additional alteration of gabbroic intrusions is likely. The fluid composition is very similar at all vent sites, indicating a common source in the reaction zone and little variation during upflow. Spatial differences in fluid composition were observed between smoking craters and the complex chimney system IRINA II, but are restricted to elements with strong temperature-controlled solubility, as Cu and Co. These differences can be related to different exit temperatures (up to 350 °C and < 300 °C, respectively). Concentrations of rare earth elements, and chondrite-normalized patterns with LREE enrichment and positive Eu anomalies are comparable to those of basaltic-hosted systems, thus indicating minor influence of host-rock composition. A comparison of published fluid composition data from 1996 [Douville, E., Charlou, J.L., Oelkers, E.H., Bienvenu, P., Jove Colon, C.F., Donval, J.P., Fouquet, Y., Prieour, D., Appriou, P., 2002. The Rainbow vent fluids (36°14'N, MAR): the influence of ultramafic rocks and phase separation on trace metal content in Mid-Atlantic Ridge hydrothermal fluids. Chemical Geology, 184: 37-48.] with our own data indicates that the system remained stable over the past nine years. There is no clear indication of phase separation taking place at Logatchev. Mineralogical and chemical composition of the rocks, reaction temperature, and partly sub-seafloor mixing with entraining seawater are supposed to be the main controlling parameters of fluid geochemistry in the Logatchev field. As it is known that more ultramafic-hosted hydrothermal systems exist along slow-spreading ridges, this type of hydrothermal systems might have a significant influence on the elemental budget of the oceans. Detailed information about the fluid geochemistry and its spatial and temporal variations is an important prerequisite for an estimation of elemental fluxes in ultramafic-hosted systems and their relative importance compared to basaltic-hosted systems. © 2007 Elsevier B.V. All rights reserved.
Keywords: HYDROTHERMAL FLUIDS; LOGATCHEV FIELD; SERPENTINIZATION; TEMPORAL VARIABILITY; ULTRAMAFIC-HOSTED HYDROTHERMAL SYSTEMS